Function of protein kinase CK2 in thrombus formation. (19th May 2019) - Ampofo, Emmanuel; Schmitt, Beate M.; Laschke, Matthias W.; Menger, Michael D.
Abstract: Thrombus formation is dependent on the interaction of platelets, leukocytes and endothelial cells as well as proteins of the coagulation cascade. This interaction is tightly controlled by phospho-regulated pathways involving protein kinase CK2. A growing number of studies have demonstrated an important role of this kinase in the regulation of primary and secondary hemostasis. Inhibition of CK2 downregulates the expression of important adhesion molecules on platelets and endothelial cells, such as glycoprotein (GP)IIb/IIIa, P-selectin, von Willebrand factor and vascular cell adhesion molecule. Moreover, the reduced CK2-dependent phosphorylation of different coagulation factors prevents the conversion of fibrinogen to fibrin. Targeting these mechanisms may open the door for the development of novel anti-thrombotic therapies.